Duration of Absence from Work Is Related to Psychopathology, Personality, and Sociodemographic Variables in a Longitudinal Cohort - Gamma, Alex; Schleifer, Roman; Warnke, Ingeborg; Ajdacic-Gross, Vladeta; Rössler, Wulf; Angst, Jules; Liebrenz, Michael (Frontiers in Psychiatry, 2017)
Objective To examine, in a non-clinical sample, the association of psychopathology, personality, socio-demographic information and psychosocial indicators of non-occupational functioning with the duration of absence from work in the past 12 months. Method A longitudinal community cohort of 591 adults from Switzerland was analyzed using multilevel ordered logistic regression, with several alternative models as robustness checks. Psychopathology was assessed using the total score (GSI) of the Symptom Check List-90 Revised (SCL-90R). Results The highest psychopathology levels were associated with absences of 3 or more weeks duration, largely independently of age. Extraversion and being divorced, widowed or separated also corresponded with longer absences from work in some analyses. No effect of sex was found. Most effects tested were not statistically significant and estimates showed large uncertainty. Conclusion Given present evidence for a link between psychopathology and occupational functioning, it is recommended that instruments for measuring psychopathology be part of expert appraisals of work ability in an insurance medical context.